Ethical Guidelines and Principles in the Context of Artificial Intelligence - de Cerqueira, José Antonio Siqueira; Tives, Heloise Acco; Canedo, Edna Dias (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
The interest in Artificial Intelligence (AI) based systems has been gaining momentum at a fast pace, both for software development teams and for society as a whole. This work aims to identify the guidelines and ethical principles for systems based on Artificial Intelligence. Design Science Research methodology was adopted in order to understand the various guidelines and principles existing in the literature. From the current landscape, a body of knowledge in the field of AI ethics is presented, with the purpose of supporting developers and Product Owners in identifying the guidelines and ethical principles in the literature so that they can be used during the software development process. Thus, this work will contribute to the various stakeholders in the development of ethical systems in the context of AI, such as: policy makers, ethicists, users, organizations, data scientists, development teams, among others.